Laho visual inclusivity and its effects on public knowledge of Philippine indigenous culture - Delfin, Alejandro Julian T.; Ilagan, Joy M. (Quezon City College of Fine Arts, University of the Philippines Diliman, 2019)
Philippine Indigenous culture has been absent in Philippine popular media within the last 5 years, with disputes coming up over the accuracy of presented visuals in fictitious television series that even remotely reference something related to indigenous Filipino elements.

If their absence continues, it is most possible that the general knowledge or idea of indigenous culture could disappear from public knowledge entirely, as noted in the idea of Symbolic Annihilation.

Despite that, many young Filipinos have a great interest in learning more about our own culture, limited only by the lack of media that would be consumable by them as an audience and it's with that in which there is actually a large untapped market.

The project aims to develop a board game in order to create a visually inclusive product that can expose young adults to Philippine indigenous culture as well as generate both awareness and a general body of knowledge by presenting numerous elements from various indigenous groups of the country.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography: leaves 181-185
Keywords: Indigenous peoples -- Philippines -- In mass media; Indigenous peoples -- Philippines -- Board games; Indigenous people